Understanding High School Students' Perceptions of Their Learning Opportunities: A Doubly Latent Approach - Dumas, Denis (Frontiers in Education, 2018)
In educational research, the amount of learning opportunities that students receive may be conceptualized as either an attribute of the context or climate in which that student attends school, or as an individual difference difference in perception of opportunity among students, driven by individual factors. This investigation aimed to inform theory-building around student learning opportunities by systematically comparing eleven theoretically plausible latent and doubly latent measurement models that differed as to the locus (i.e., student- or school-level) and dimensional structure of these learning opportunities. A large (N = 963) and diverse sample of high-school students, attending nine fifteen different high-schools, was analyzed. Results suggested that student learning opportunities are best conceptualized as distinct but positively correlated factors, and that these doubly latent factors occurred at the student level, although with a statistical correction for school-based clustering. In this way, student learning opportunities may be best described as individual perceptions, rather than an indicator of school climate or context. In general, these results are expected to inform current conceptualizations of student learning opportunities within schools, and function as an example of the substantive inferences that can be garnered from multi-level measurement modeling.